Description of the Nutritional Status of Pregnant Women in the Work Area of Malintang Community Health Center - Nurkholidah; Siti Khadijah Batubara (International Journal of Public Health Excellence (IJPHE), 2022)
Nutritional status is an expression of a state of balance in the form of certain variables, or the manifestation of nutrition in the form of certain variables. In Indonesia, the LBW threshold with the risk of SEZ is estimated to give birth to LBW babies. If the baby is born with low birth weight (LBW) will have a risk of death, malnutrition, growth disorders, and child development disorders. To prevent the risk of CED in pregnant women before pregnancy, women of childbearing age must have good nutrition. This study aims to determine the nutritional status of pregnant women in the working area of the Malintang Public Health Center, Bukit Malintang District, Mandailing Natal Regency . This research is descriptive, as many as 35 respondents. From the results of the study, it was found that the nutritional status of pregnant women based on normal weight gain was 30 respondents (85.71%) and less weight gain was 5 respondents (14.28%), based on LBW the majority of normal LBW were 30 respondents (85.71). %) and LBW less than 23.5 cm as many as 5 respondents (14.28%), and based on the adequacy of adequate nutritional intake as many as 30 respondents (85.71%) and the adequacy of insufficient nutritional intake as many as 5 respondents (14.28%). Based on the results of the study, it can be concluded that the nutritional status of pregnant women in the Malintang Health Center Work Area is to further improve the health service program for pregnant women.